Culture and the social-ecology of local food use by Indigenous communities in northern North America - Roxanne Tremblay (Resilience Alliance, 2020)
Social-ecological and biocultural systems connect people to their environment at the intersection of nature and culture. The harvest of local wildlife for human consumption is critically important to the food security of the world's Indigenous peoples and to the conservation of biodiversity, either as a driver of biodiversity loss or of biodiversity protection, depending on system properties. By their nature, local food systems are assumed to be both ecologically determined and culturally defined. Here, we analyze standardized local food consumption surveys conducted in 21 Indigenous communities across northern North America. Using measures of dietary similarity from the ecological sciences and a variance partitioning statistical approach, we reveal a profound and prevailing importance of culture in defining the types and amounts of animal species consumed as food, operating within the environmental constraint of local availability. This quantitative, multicommunity analysis reveals the sustainability and cultural agency inherent in local food systems and the importance of cultural-ecological coupling in an era of accelerating social and environmental change.